2016
DOI: 10.3168/jds.2016-11131
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of konjac glucomannan as a fat replacer in low-fat and skimmed yogurt

Abstract: Konjac glucomannan (KGM) has been reported to be beneficial to human health, as well as having potential functional properties as a fat replacer in dairy products. In this study, 0.5% KGM solution was added to prepare low-fat (LFKGM) and skimmed (SKKGM) yogurts, and their physicochemical properties were compared with those of full-fat yogurt control (FFC), low-fat yogurt control (LFC), and skimmed yogurt control (SKC). Properties and composition were determined and the microscopic structures of all yogurts wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 44 publications
4
30
3
Order By: Relevance
“…for glucomannan production, a kind of low digestive and neutral carbohydrate that applicable to be used in food, beverage, pharmacy and other strategic industries (Haryani and Hargono, 2008;Sugiyama and Santosa, 2008;Keithley et al, 2013;Hananto et al, 2015;Dai et al, 2016;Yang et al, 2017). From 100 g dried chips, about 20-31 g pure glucomannan is obtained depend on extraction method (Dwiyono, 2014;Widjanarko and Suwasito, 2014).…”
Section: Evaluasi Hasil Klon Terpilih Apomiktik Iles-iles (Amorphophamentioning
confidence: 99%
“…for glucomannan production, a kind of low digestive and neutral carbohydrate that applicable to be used in food, beverage, pharmacy and other strategic industries (Haryani and Hargono, 2008;Sugiyama and Santosa, 2008;Keithley et al, 2013;Hananto et al, 2015;Dai et al, 2016;Yang et al, 2017). From 100 g dried chips, about 20-31 g pure glucomannan is obtained depend on extraction method (Dwiyono, 2014;Widjanarko and Suwasito, 2014).…”
Section: Evaluasi Hasil Klon Terpilih Apomiktik Iles-iles (Amorphophamentioning
confidence: 99%
“…Data were recorded using Texture Proc CT V1.3 Build 15 software (Brookfield Engineering Laboratories Inc.). Yogurt samples (200 g) were tested in 250-mL Corning polypropylene cone beakers (Sigma-Aldrich, St. Louis, MO) using the following compression test setting: target distance = 30.0 mm; trigger load = 10 g; test speed = 1.00 mm/s; return speed = 1.00 mm/s (Dai et al, 2016). The parameters determined were hardness, total work done, adhesive force, and adhesiveness.…”
Section: Texture Analysismentioning
confidence: 99%
“…Syneresis was measured using the drainage method used by Dai et al (2016). Approximately 25 g of yogurt sample was weighed on a 2-V folded filter paper (qualitative, catalog no.…”
Section: Syneresismentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, hydrocolloids are widely used in food formulations to mimic fat and compensate the physicochemical changes due to lipid reduction. Several studies have shown the effectiveness of KGM as fat replacer in the formulation of reduced‐fat products for applications such as meat products, sausages, low‐fat bologna, mayonnaise, and dairy products: low‐fat and skimmed yogurt, cheese …”
Section: Overview Of Kgmmentioning
confidence: 99%